Preferences of market gardeners for traditional vegetables and associated factors in urban areas of Southern Benin - KOUEVI, TEKO AUGUSTIN; ADE, K. Claude; N'Danikou, Sognigbé; MONGBO, ROCH LAMBERT; Komlan, Marie Christelle; DAGNON, Gaïane Naïla; DJOSSOUVI, Céphas O.E.A.; Legba, Eric Cocou; Achigan-Dako, Enoch G (My University, 2023)
There is a growing interest in the promotion of the use of traditional vegetables to reduce micronutrient and dietary fibres gaps among food consumers, and to support rural and urban livelihoods in sub–Saharan Africa, including in Benin, because they are considered more nutritious, accessible, and more culturally acceptable for local people than many exotic vegetables. Meanwhile, the extent to which these traditional vegetables are preferred by the target populations, especially by the local market gardeners who supply consumers, is not yet well-known in the context of Benin, specifically in its large cities of Abomey-Calavi and Cotonou. This paper fills this knowledge gap by analysing the preferences and the factors affecting the preferences of market gardeners for traditional vegetables in these cities. To achieve this objective, field visits and observations took place, as well as interviews with managers of market gardeners' organisations, and with market gardeners randomly selected in both cities. Data analysis revealed that a wide range of vegetables is produced in the study areas, including in decreasing order of importance, leafy (5 traditional and 1 exotic), fruit (3 traditional and 1 exotic), flower (0 traditional and 1 exotic), root (0 traditional and 1 exotic), and bulb (1 traditional and 0 exotic) vegetables. It was also noted that the production of traditional vegetables was preferred to that of exotic ones. The logistic regression model executed indicated that “market gardeners group membership”, “resistance to pests”, and “clients’ demands” significantly and positively influence traditional crops’ choice by the gardeners. In contrast, “several years of market gardening experience”, “land loan”, and “profitability” significantly and negatively influence the choice of traditional vegetable production by the surveyed gardeners. Overall, it appeared from the study that economic interests and technical constraints are the main reasons guiding the market gardeners' production preferences and that leafy, fruit, and bulb traditional vegetables are most demanded by consumers. These findings suggest that Cotonou and Abomey-Calavi are relevant places for the promotion of traditional vegetable production.
Keywords: Food and nutrition security; Traditional African market garden vegetables; Market gardeners’ preferences’ study; Municipalities of Abomey-Calavi and Cotonou; Republic of Benin